Dielectric silicone elastomers filled with in situ generated polar silsesquioxanes: Preparation, characterization and evaluation of electromechanical performance. (15th September 2016) - Bele, Adrian; Dascalu, Mihaela; Tugui, Codrin; Iacob, Mihail; Racles, Carmen; Sacarescu, Liviu; Cazacu, Maria
Abstract: Dielectric silicone elastomers able to respond to an electrical stimulus by a mechanical displacement are prepared through a simple one-pot procedure consisting in cross-linking and simultaneous in situ generation of the filler functionalized with polar groups, as reinforcing and dielectric permittivity enhancer. One and the same reagent, (3-chloropropyl)trimethoxysilane (CPTMS), serves as both cross-linker and precursor for the filler. This is incorporated in different amounts with dibutyltindilaurate (DBTDL) into polydimethylsiloxane-α, ω-diols having molecular masses of 34, 500 and 125, 000 g ⋅ mol − 1 and left for curing in atmospheric conditions. The Fourier Transform Infrared (FTIR) spectra show absorption bands characteristic for silsesquioxane (SSQ) structures formed by converting excess CPTMS, while the Transmission Electron Microscopy (TEM) images reveal biphasic morphology of the resulting material in which formations which we have assumed to be SSQ are distributed within the silicone matrix. The structural aspects and supramolecular organization are investigated by Wide Angle X-Ray Diffraction (WAXD) and Small Angle X-ray Scattering (SAXS) analysis. The influence of the CPTMS amount over the mechanical and dielectric properties of the resulted materials are investigated expecting an improvement of the dielectric permittivity but also a strengthening of material. Lateral strain as a response to an applied voltage on dielectric films is measured. Graphical abstract: The simultaneous crosslinking and in situ generation of the filler having polar groups as a dielectric permittivity enhancer for polydimethylsiloxanes were performed by using a unique chemical as agent/precursor in a one-pot procedure to easily produce dielectric elastomer films suitable for actuation. Highlights: (3-Chloropropyl)trimethoxysilane was used as polar crosslinker and filler`s precursor for silicones in an one pot procedure; The formation of silsesquioxane structures bearing polar groups within silicone matrix has been proven; Increase of 74.8% in lateral strain was obtained by inserting 15 wt% crosslinker in a polydimethylsiloxane of 34, 500 g/mol; Increase of 37.1% in dielectric strength resulted by adding 5 wt% crosslinker to a polydimethylsiloxane of 125, 000 g/mol.